How Brazil's sustainable cattle schemes could beef up to conserve forests and sustainable rural livelihoods - Maguire-Rajpaul, Victoria Alice; Galuchi, Tharic; Nery Alves Pinto, Helena; McDermott, Constance (2016)
Cattle ranching is the largest driver of Brazilian deforestation, a relevant emitter of greenhouse gases, and an important source of local livelihoods. In response, many initiatives attempt to render Brazil’s beef production more environmentally and socially sustainable. Drawing on key informant interviews, this paper assesses the effectiveness of Brazil’s sustainable cattle schemes, with a particular focus on avoided deforestation in the Amazon biome; climate change mitigation; and improving the livelihoods of smallholder ranchers. We found that the sustainable cattle schemes have yet to reach scale and have yet to effectively halt forest loss, reduce greenhouse gas emissions, or sustain rural livelihoods. Thus far, cattle moratoria have achieved the greatest scale in addressing deforestation, but only by targeting the largest and thus most resourced ranches. In order to achieve both socially and environmentally sustainable cattle production, Brazil’s sustainable cattle schemes must scale up, and all governance groups interviewed recommended bottom-up, technical assistance to ranchers to achieve this. Mixed governance schemes, involving both state and non-state actors, were also widely advocated. Impacts were difficult to compare due to a lack of uniform monitoring and thus comparability across the schemes; tools for common measurement are recommended to better compare schemes’ effectiveness. The greatest perceived barriers were market-based: namely the lack of a sustainable beef brand and the associated lack of consumer demand. Respondents also noted the need for improved agronomic and technical assistance for ranchers. Social considerations in the schemes were found to be vague, and in some schemes, neglected.